INNOVATIVE CHANGES IN THE FIELD OF PHYSICAL EDUCATION AND PHYSICAL CULTURE - Ikromjon Yuldashov (Western European Studies, 2024)
The process of physical education is multifaceted. In this process, both education and upbringing are given. In the process of physical education, education will be focused on the formation and improvement of motor skills, abilities. At the same time, the physical development of the trainees is affected. Creating a healthy lifestyle in our society, creating modern conditions for regular physical culture and mass sports of the population, especially the younger generation, strengthening confidence in the will, strength and capabilities of young people through sports competitions, courage and patriotism, motherhood Extensive work is being done to develop a sense of devotion to the motherland, as well as the systematic organization of the selection of talented athletes among young people and the further development of physical culture and mass sports.
Keywords: physical culture; physical education theory; health